Epidemiological Analysis of Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae Outbreak in a Neonatal Clinic in Poland - Agata Pruss; Paweł Kwiatkowski; Helena Masiuk; Iwona Bilska; Stefania Giedrys-Kalemba; Barbara Dołęgowska (MDPI AG, 2022)
Klebsiella pneumoniae is one of the most common etiological agents isolated from epidemic outbreaks in neonatal wards. We describe how an extended-spectrum β-lactamase-producing K. pneumoniae (ESBL-KP) outbreak in a neonatal ward was extinguished. During the outbreak, which lasted over two months, 26 neonates were tested for K. pneumoniae, and 42 environmental swabs were taken. Drug susceptibility was determined for the isolated strains, and their virulence and phylogenetic similarity were checked. ESBL-KP colonization was confirmed in 18 neonates, and six were also confirmed to be infected. All strains isolated from patients represented one clonal type, K. pneumoniae. One strain isolated from an environmental source was determined to be a unique pulsed-field gel electrophoresis pattern. Gestational age and Apgar score were assessed as statistically significant for neonates with ESBL-KP infection. The epidemiological measures taken have been successful, and no further cases appeared. Immediate tightening of hospital hygiene rules, screening of all hospitalized neonates, and cohorting ESBL-KP-positive patients proved effective in controlling and ending the outbreak. The lack of ESBL-KP in the environment suggests that the outbreak was transmitted by colonized hospital staff. This theory could be confirmed by introducing mandatory screening for medical personnel.